The Effect of Moodle Learning Media on Students' Mathematics Learning Outcomes - Muh Hamkah; A. Muh. Ali; Sahra (Digital Pedagogy in Primary Education Journal, 2026)
This study aims to determine the effect of Moodle learning media on elementary school students' mathematics learning outcomes in Makassar City. The study used a quantitative approach with an ex-post facto design. The research population consisted of fifth-grade elementary school students, with a sample of fifth-grade students from the Tidung State Elementary School UPT SPF with three learning groups who had participated in mathematics learning using the Moodle learning media, with a total of 142 student respondents. Data collection was conducted using a Likert scale questionnaire to measure the use of the Moodle learning media and a learning outcome test to measure students' mathematics learning outcomes. The data obtained were analyzed using descriptive statistics and simple linear regression analysis with the help of the SPSS program. The results of the descriptive analysis showed that the use of Moodle learning media was in the high category with an average score of 77.80, while the students' mathematics learning outcomes were also in the high category with an average score of 78.90. The regression test results showed that Moodle learning media had a positive and significant effect on students' mathematics learning outcomes with a regression coefficient value of 0.50 and significance of 0.000 < 0.05. Based on the results of this study, it can be concluded that Moodle learning media has a significant effect on the mathematics learning outcomes of elementary school students in Makassar City. Therefore, the use of Moodle as a technology-based learning medium needs to be optimized to improve the quality of mathematics learning. Keywords: Mathematics Learning Outcomes, Moodle Learning Media, Technology-Based Learning.